Implementation of the Centro Nacional Chega! I.P Programme to Promote Transitional Justice for the Rights of Survivors - Liliana Fransisco da Costa de Jesus; Jose Cornelio Guterres; Leonito Madeira Martins (CV. Ulil Albab Corp, 2024)
The aim of the research are to study, analyze and describe the implementation programme of the CNC! I.P to promote transitional justice, especially the right to reparation for victims in depth. The author uses a theoretical reference in the form of Institutional Theory (Grand Theory) according to Scott and Fitrianto (2008) stating that institutional theory is an organization that prioritizes legitimacy and opportunities regarding social expectations in the organization. And it is also equipped with other supporting theories such as: Implementation Theory, Transitional Justice Theory, Reparation Theory and Definition of Victims to support the process of preparing this thesis. The author uses descriptive qualitative research methods in describing the results of existing research regarding CNC! I.P Implementation Programme, especially reparations or restoration for victims. The research informants in question were CNC! I. P implementers, AJAR, Educators, and also victims, totaling 9 peoples. The collection technique used in this research was; observation, interviews and documentation and interactive model data analysis techniques'. The conclusion of all existing research results regarding the implementation of the CNC! I. P program in implementing transitional justice, especially the right to reparation for victims, has implemented several programs such as social services for victims and their families in the aspects of health, housing, economics and education based on the formulation of Decree-Law No.48/2016 and is based on the recommendations of the Comissão Acolhamento Verdade e Reconciliação (CAVR) and the Comissão Verdade e Amizade (CVA). Reparations for victims aim to rehabilitate, respect, restore and guarantee a decent life for the victims. However, its implementation has not been optimal due to the minimal allocation of funds based on the victim's eligibility conditions, there has not been a specific legal resolution as a legal scheme for respecting and restoring the rights and conditions of victims, it is necessary to reform institutions, especially the court system so that it is able to enforce the law against actors. violence and also the need to create Peace education so that it can develop people's character and mentality so that they do not repeat violence in the past.